Problems of Islamic Religious Education Teachers in Improving Professionalism in the Modern Era - Eliyatul Fitriyah (Al-Alim: Jurnal Pendidikan Agama Islam, 2026)
This study aims to analyze the problems of Islamic Religious Education (PAI) teacher professionalism in the modern era, characterized by the development of information technology and complex socio-religious changes. This study uses library research methods by reviewing academic literature, government policies, and relevant previous research results. The novelty of this study lies in a holistic analytical approach that integrates four main aspects of teacher professionalism: qualifications and competencies, welfare, training and certification, and recruitment and development. The results show that the main problems lie in the low suitability of academic qualifications, welfare inequality between regions, a weak training and certification system that is still administrative, and a recruitment and development process that is not based on meritocracy and equal distribution of needs. To address these issues, this study recommends strengthening policies to improve academic qualifications through the Recognition of Prior Learning (RPL) and Distance Learning programs, improving the allowance system and funding partnerships based on ZISWAF, reforming training based on field needs (need assessment), and continuous professional development through mentoring and professional learning communities.